2021
DOI: 10.1097/rli.0000000000000839
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Image Conversion Improves the Reproducibility of Computed Tomography Radiomics Features

Abstract: Objectives: This study aimed to evaluate the usefulness of deep learning-based image conversion to improve the reproducibility of computed tomography (CT) radiomics features. Materials and Methods: This study was conducted using an abdominal phantom with liver nodules. We developed an image conversion algorithm using a residual feature aggregation network to reproduce radiomics features with CT images under various CT protocols and reconstruction kernels. External validation was performed using images from dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 36 publications
1
15
1
Order By: Relevance
“…Our results confirm limitations in the use of many features in conjunction with FBP and iterative reconstruction but also reveal novel opportunities with deep learning reconstruction that may be considered in retrospective data collection and future protocol implementations for radiomics [26]. Moreover, our results underline that the integration of deep learning into image processing has high potential to improve radiomics research, supporting conclusions from previous reproducibility studies [22,23].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results confirm limitations in the use of many features in conjunction with FBP and iterative reconstruction but also reveal novel opportunities with deep learning reconstruction that may be considered in retrospective data collection and future protocol implementations for radiomics [26]. Moreover, our results underline that the integration of deep learning into image processing has high potential to improve radiomics research, supporting conclusions from previous reproducibility studies [22,23].…”
Section: Discussionsupporting
confidence: 80%
“…We independently assessed four reconstruction algorithms for radiomics feature extraction, and our investigation encompassed the entire imaging chain including raw data acquisition. Our study thus differed from previous work, in which an image conversion filter was applied to reconstructed image data [22,23]. The phantom we used had the advantage of featuring complex textures similar to human tissues, enabling us to evaluate feature stability and discriminative power in a realistic setting.…”
Section: Discussionmentioning
confidence: 98%
“…Lee et al [ 13 ] proposed a GAN to improve the reproducibility of CT-based radiomics features. We employed a generator network (G) architecture, including a hierarchical feature synthesis module from a prior study [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study reported a deep learning algorithm capable of converting various computed tomography (CT) images derived from diverse CT protocols into target CT images [ 13 ]. This study used a generative adversarial network (GAN) to standardize CT images to improve the reproducibility of radiomics features.…”
Section: Introductionmentioning
confidence: 99%
“…DLR improves image quality compared with FBP or IR 18 20 and facilitates dose reduction while maintaining the image quality and diagnostic performance of CT scans 21 . The effect of other deep learning-based technology, for example, deep learning-based conversion of reconstruction kernel, on the reproducibility of radiomic features has been studied before 22 , 23 . However, the effects of DLR on radiomic features have not yet been compared to other reconstruction methods.…”
Section: Introductionmentioning
confidence: 99%